The Wayward Bus Movie Still - Twentieth Century Fox Film Corporation:::Creator::::::::::::
Camille Oaks (Jayne Mansfield) sits with Norma (Betty Lou Keim) on bus as Ernest Horton (Dan Dailey) watches them in background. RESTRICTED USE